Effectiveness of a Short Education Movie on Family Knowledge of Pulmonary Tuberculosis Transmission: A Quasi-Experimental Study - Ecki Salma Hapsari; Dadang Kusbiantoro; Arifal Aris (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Household members of patients with pulmonary tuberculosis are at increased risk of infection because of prolonged exposure and often have inadequate knowledge regarding disease transmission. Health education using audiovisual media, such as a Short Education Movie (SEM), may improve understanding of tuberculosis transmission; however, evidence regarding its effectiveness among family members in primary healthcare settings remains limited. Objective: This study aimed to evaluate the effect of Short Education Movie (SEM)–based health education on family members' knowledge of pulmonary tuberculosis transmission at a primary healthcare center. Methods: A quantitative quasi-experimental study with a one-group pretest–posttest design was conducted at Mantup Community Health Center, Lamongan, Indonesia, from May to June 2026. Fifty-four family members of patients with pulmonary tuberculosis were recruited using accidental sampling. Participants completed a researcher-developed 15-item knowledge questionnaire before and immediately after receiving a single SEM-based educational intervention. Descriptive statistics were used to summarize participant characteristics and knowledge scores. Differences between pretest and posttest scores were analyzed using the Wilcoxon Signed-Rank Test, with statistical significance set at p < 0.05. Results: The mean knowledge score increased from 8.59 ± 2.54 before the intervention to 12.87 ± 1.69 after the intervention. The proportion of participants with good knowledge increased from 13.0% at baseline to 70.4% following the intervention, whereas the proportion with poor knowledge decreased from 59.3% to 3.7%. The Wilcoxon Signed-Rank Test demonstrated a statistically significant improvement in knowledge after the intervention (p < 0.001). Conclusion: Short Education Movie–based health education significantly improved family members' knowledge of pulmonary tuberculosis transmission. SEM represents a practical and effective educational strategy for strengthening family-centered tuberculosis prevention and may support the integration of standardized audiovisual education into community nursing practice and primary healthcare tuberculosis control programs